Determination of the most dangerous flight modes of aircraft in icing conditions - S. R. Bokov; V. V. Efimov (Научный вестник МГТУ ГА)
In this paper, the object of research is the icing of aircraft surfaces during flight in the atmosphere. On many light aircraft, as well as on unmanned aircraft weighing less than 30 kg, there are no on-board de-icing systems. Nevertheless, aviation events occur with these aircraft, which are a consequence of their icing. Therefore, determining the most dangerous flight modes of aircraft in icing conditions is an urgent task. In view of the high cost of conducting flight tests and the impossibility of covering all possible events due to their potential danger, the complexity of creating flight conditions for aircraft in icing conditions on the ground, the mathematical modeling method was used in this study. To solve this problem, the analysis of the airworthiness standards of civil light aircraft, transport category aircraft, rotorcraft of normal and transport category was carried out within the framework of the work, the influence of various parameters on the thickness of ice build-up was investigated using a computational experiment conducted on the software developed by the authors of the article. On the basis of the results of the computational experiment, the dependences of the ice thickness on various icing parameters were obtained, a method was developed for determining the combination of heights and flight speeds of an aircraft, at which ice of the greatest thickness is formed on the surface of aircraft, other things being equal. Possession of this information will allow the aircraft crew and air traffic control specialists to avoid the most dangerous flight modes in terms of icing.